Nurturing Resilient Communities: Unveiling the Transformative Potential of Agroecological Preservation in Sustainable Farming - Conadera , Rony (Journal of Interdisciplinary Perspectives, 2024)
This study delves into the exploration of agroecological preservation patterns in the Municipality of Lambunao. The main objective is to understand the current practices and their implications on the local environment. To achieve this, a descriptive research method was employed, utilizing a standardized data-gathering instrument to collect information from 500 local community farmers, selected through random stratified sampling across various barangays. The research method involved the use of descriptive statistics, including frequency count and ranking, for data analysis. Additionally, inferential research was conducted using the Mann-Whitney U test and Kruskall Wallis test, with a significance level set at 0.05. The results of the study revealed that the Agroecological System in Lambunao is primarily characterized by plain topography, clay soil type, and rice as the main crop. The farmers predominantly practice organic farming as a tradition. Preservation practices were found to be frequently practiced by the entire group and seldom practiced when considering selected variables. However, when focusing on the tradition of organic farming, it was found that farmers always practiced preservation. The study concluded that there were no significant differences in preservation practices in terms of age, sex, selected educational attainment, and number of years in farming. However, significant differences were found in farm land area and selected categories of educational attainment. In conclusion, the study underscores the importance of organic farming and the need to promote preservation practices among local community farmers, offering valuable insights into the agroecological preservation patterns in the Municipality of Lambunao.